Effect of geochemical conditions on PFAS release from AFFF-impacted saturated soil columns. Issue 3 (11th January 2023) - Nickerson, Anastasia; Maizel, Andrew C.; Schaefer, Charles E.; Ranville, James F.; Higgins, Christopher P.
Abstract : Certain PFAS, such as 4:2 fluorotelomer sulfonate, eluted faster from high pH, high sodium columns compared to neutral columns packed with field-collected soil. Other PFAS had more mass eluted from the high pH, high sodium columns. Abstract : Per- and polyfluoroalkyl substances (PFASs) are frequently found at high concentrations in the subsurface of aqueous film forming foam (AFFF)-impacted sites. Geochemical parameters affect the release of PFASs from source area soils into groundwater but have not been extensively studied for soils that have been historically impacted with AFFF. This study investigated the effects of pH and salt concentrations on release of anionic and zwitterionic PFASs from AFFF-impacted soils in flow-through saturated columns. High pH (10) columns with elevated sodium concentrations had higher cumulative masses eluted of several PFASs compared to pH 3 and pH 7 columns with lower sodium concentrations, likely caused by changes to soil organic matter surface charge. Four PFASs ( e.g. 4:2 fluorotelomer sulfonate, perfluorobutane sulfonamido acetic acid) eluted significantly earlier in both pH 3 and pH 10/high NaCl columns compared to pH 7 columns. The results of this study suggest that shifts in pH for soils located at AFFF-impacted sites – particularly raising the pH – may mobilize sorbed PFASs, specifically longer-chain and zwitterionic compounds that are typically strongly sorbed to soil.